First Report on the Characteristics of Methicillin-Resistant Staphylococcus Capitis Isolates and an NRCS-A-clone Related Isolate Obtained from Iranian Children - Asadollahi, Parisa; Farzan, Behrooz; Rezaei, Faranak; Delfani, Somayeh; Ashrafi, Behnam; Soroush, Setareh (Infectious Disorders - Drug Targets, 2021)
Background: Methicillin-resistant staphylococcus capitis (MRSC) NRCS-A clone (Multi- resistant and vancomycin-non susceptible) has been recently described as an emerging cause of nosocomial bacteremia, especially in neonatal intensive-care units (NICUs). Objective: The objective of this study was to evaluate the antibiotic and antiseptic resistance patterns, biofilm-producing ability and the prevalence of SCCmec and ACME types among MRSC isolates as well as to check the possible presence of NRCS-A clone at Tehran’s Children's Medical Center, Iran. Methods: A total of 256 coagulase-negative Staphylococcal isolates were collected, of which 10 S. capitis isolates were obtained and tested for susceptibility against 13 antimicrobial and 3 antiseptic agents, as well as biofilm production. The presence of 15 distinct resistance genes, staphylococcal cassette chromosome mec (SCCmec), and arginine catabolic mobile elements (ACMEs) were tracked. Results: Seven out of 10 S. capitis isolates were MRSC (MIC90 van=8μg/mL) and resistant to trimethoprim/sulfamethoxazole, produced biofilm, (3 as strong biofilm producers) and carried ACME types I and II. Despite the identification of mec and ccr complexes in some isolates, all the SCCmec cassettes were untypeable (UT). Conclusion: According to the studied features, only one isolate belonged to the NRSC-A clone. The results indicate that MRSC with high antibiotic resistance and unknown SCCmec might become a serious problem in the future for the treatment of patients, particularly children.
Keywords: NRCS-A clone